2004
DOI: 10.1023/b:prev.0000045360.23290.8f
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and Alcohol Use as an Explanation for the Association Between Externalizing Behavior and Illicit Drug Use Among Delinquent Adolescents

Abstract: The prevalence and persistence of adolescent substance use and abuse is a national health issue, and substance use among adolescents is frequently comorbid with other psychiatric disorders. Most studies in this area utilize samples of middle or high school students or from inpatient settings. Less is known about substance use and psychiatric comorbidity among delinquent adolescents. The present study examined data from two cohorts of juvenile offenders collected over a 2-year period (n = 245, n = 299). Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 34 publications
5
40
0
6
Order By: Relevance
“…Externalizing problems are consistent predictors of adolescent substance use (Helstrom et al, 2004), with delinquent behavior one of the most consistent risk factors for drinking initiation (Donovan, 2004). The relationship between substance involvement and internalizing problems such as depression or anxiety is less established, although several studies have found internalizing symptoms to be associated with adolescent substance use (Lewinsohn et al, 1995;McCarty et al, 2012).…”
mentioning
confidence: 99%
“…Externalizing problems are consistent predictors of adolescent substance use (Helstrom et al, 2004), with delinquent behavior one of the most consistent risk factors for drinking initiation (Donovan, 2004). The relationship between substance involvement and internalizing problems such as depression or anxiety is less established, although several studies have found internalizing symptoms to be associated with adolescent substance use (Lewinsohn et al, 1995;McCarty et al, 2012).…”
mentioning
confidence: 99%
“…It is known that smoking is closely related to juvenile delinquency (33). Smoking poses a risk for both health and substance abuse (34). It has been suggested that smoking in juveniles draged to crime is associated with an inadequate social support (35).…”
Section: Discussionmentioning
confidence: 99%
“…O flagelo do uso de drogas não está restrito ao Brasil, é um problema internacional de saúde como pode ser comprovado por pesquisas realizadas na: Oceania = Austrália; Ásia = Índia e Tailândia; na Europa = Espanha; e América do Norte = Estados Unidos, que apontam o uso de substâncias psicoativas como fator indutor da delinqüência (DURANT; KNIGHT; GOODMAN, 1997;CROWLEY et al, 1998;AMITI-MACKESY;FENDRICH, 1999;KUO et al, 2002;GONZALVO, 2002;BELENKO;LOGAN, 2003;HELSTROM et al, 2004;SWAHN;DONOVAN, 2004;KIM;KIM, 2005;LENNINGS;KENNY;NELSON, 2006).…”
Section: Introductionunclassified